2001
DOI: 10.1093/oxfordjournals.molbev.a003761
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based Phylogenetic Analysis of Short-chain Alcohol Dehydrogenases and Reclassification of the 17beta-Hydroxysteroid Dehydrogenase Family

Abstract: Short-chain alcohol dehydrogenases (SCAD) constitute a large and diverse family of ancient origin. Several of its members play an important role in human physiology and disease, especially in the metabolism of steroid substrates (e.g., prostaglandins, estrogens, androgens, and corticosteroids). Their involvement in common human disorders such as endocrine-related cancer, osteoporosis, and Alzheimer disease makes them an important candidate for drug targets. Recent phylogenetic analysis of SCAD is incomplete an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Other normalizations of RMS distances in structural alignments have been used to construct structure-based phylogenies (4,5,16,22,26). In those studies the normalized RMS distances were used as the values in a distance matrix and distance-based phylogenies were constructed using unweighted pair group method with averages (UPGMA) or neighbor-joining methods.…”
Section: Resultsmentioning
confidence: 99%
“…Other normalizations of RMS distances in structural alignments have been used to construct structure-based phylogenies (4,5,16,22,26). In those studies the normalized RMS distances were used as the values in a distance matrix and distance-based phylogenies were constructed using unweighted pair group method with averages (UPGMA) or neighbor-joining methods.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, two putative catalytic sites of the short-chain dehydrogenase/reductase family were identified in the TER amino acid sequence. Most proteins of this family possess a catalytic site with consensus motif YXXXK (37,40,41), and some show a modified motif with YX 3-7 K (42, 43). TER from Euglena possesses the motif YX 6 K at residues 231-238 and YX 5 K at residues 279 -285 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, opposite results have been reported, as in some studies the truncated HSD17B7 protein was found to be inactive (Marijanovic et al 2003). Owing to its amino acid sequence similarity with the yeast ERG27 protein, the HSD17B7 enzyme was also suggested to possess a 3-ketosteroid reductase activity (Breitling et al 2001a,b, Marijanovic et al 2003. Accordingly, in vitro, both the human and the mouse HSD17B7 enzymes have been shown to catalyse the conversion of zymosterone to zymosterol (Marijanovic et al 2003), an essential reaction in the cholesterol biosynthesis.…”
Section: Hsd17b7mentioning
confidence: 92%